Enhancing Chemistry Learning through Digital Platforms: Teachers’ Practices and Students’ Engagement in Morogoro Secondary Schools, Tanzania - Faraja Willy; Prospery Mwansa Mwila (Journal of Education and Teacher Training Innovation, 2025)
The study examined the influence of digital learning platforms on students’ understanding and application of Chemistry concepts in public secondary schools in Morogoro, Tanzania. It aimed to explore the types of digital platforms employed by teachers, assess the extent of their classroom integration, and evaluate their effects on students’ learning outcomes. A mixed-methods approach was used, combining questionnaires, interviews, lesson plan analysis, and classroom observations. Data were collected from 52 students, 10 Chemistry teachers, and school administrators across selected schools. Findings revealed that while teachers demonstrated high awareness of digital learning platforms and frequently used them during lesson preparation, classroom integration remained inconsistent. Students reported partial exposure, with only 52% observing the use of digital tools during lessons. Teachers predominantly relied on user-friendly resources such as YouTube educational channels and national online platforms (Shule Direct, TIE, Mwalimu Plus), whereas sophisticated Learning Management Systems were minimally utilized. Observations and student feedback highlighted positive effects of digital platforms on conceptual understanding, problem-solving, visualization of abstract concepts, engagement, motivation, and collaborative learning. Challenges included limited infrastructure, unreliable internet, inadequate technical support, and underutilization of advanced digital tools. These findings align with the Technology Acceptance Model (TAM) and TPACK framework, emphasizing the need for both perceived usefulness and ease of use, along with pedagogical integration, to optimize digital learning. The study recommends enhancing infrastructure, providing continuous professional development, promoting LMS adoption, and fostering institutional policies that support systematic digital integration in Chemistry instruction to maximize learning outcomes.